2011
DOI: 10.1002/polb.22256
|View full text |Cite
|
Sign up to set email alerts
|

Natural underwater adhesives

Abstract: The general topic of this review is protein-based underwater adhesives produced by aquatic organisms. The focus is on mechanisms of interfacial adhesion to native surfaces and controlled underwater solidification of natural water-borne adhesives. Four genera that exemplify the broad range of function, general mechanistic features, and unique adaptations are discussed in detail: blue mussels, acorn barnacles, sandcastle worms, and freshwater caddisfly larva. Aquatic surfaces in nature are charged and in equilib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
298
0
5

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 292 publications
(310 citation statements)
references
References 131 publications
(140 reference statements)
1
298
0
5
Order By: Relevance
“…Charge separation has also been observed in an adhesive protein of the sandcastle worm (Phragmatopoma californica), pc-3A, which has an acidic N-terminus and basic C-terminus (Wang & Stewart 2012). Like zebra mussels, sandcastle worms also contain both acidic and basic proteins (Endrizzi & Stewart 2009;Stewart et al 2011). It has been suggested that such segregation of charges indicates a possible role for complex coacervation in the adhesion process of marine mussels and sandcastle worms, which has several advantages for underwater adhesion, as recently reviewed elsewhere (Lee et al 2011).…”
Section: Dpfp5mentioning
confidence: 91%
“…Charge separation has also been observed in an adhesive protein of the sandcastle worm (Phragmatopoma californica), pc-3A, which has an acidic N-terminus and basic C-terminus (Wang & Stewart 2012). Like zebra mussels, sandcastle worms also contain both acidic and basic proteins (Endrizzi & Stewart 2009;Stewart et al 2011). It has been suggested that such segregation of charges indicates a possible role for complex coacervation in the adhesion process of marine mussels and sandcastle worms, which has several advantages for underwater adhesion, as recently reviewed elsewhere (Lee et al 2011).…”
Section: Dpfp5mentioning
confidence: 91%
“…6,7 Coacervation benefits adhesion in several important ways: (1) high polymer concentration increases density, (2) the low interfacial energy improves wetting, (3) high diffusivity maintains good mixing, and (4) reduced viscosity eases delivery. 1 Mfp-3s is localized to the plaque−substratum interface ( Figure 1b) together with mfp-3f and mfp-5. Due to its amphiphilic and ampholytic structural characteristics (Figure 2a), mfp-3s is capable of self-coacervation 8 and is more stable at oxidation than other mfps.…”
mentioning
confidence: 99%
“…In aqueous environments, the capacity of materials to wet and de-wet plays an important role in the interfacial dynamics between the substrate, water and adhesives of fouling organisms Petrone 2013). Such sessile organisms have developed specialised sensory systems that enable them to find optimal substrates via detection of surface physicochemical features (Clare & Nott 1994;Callow et al 2005;Aldred et al 2006;Bielecki et al 2009;Stewart et al 2011). Many fouling organisms, such as barnacles and mussels, have evolved adhesive secretions with superior abilities compared to synthetic glues, to attach to submerged surfaces with diverse properties (Nott 1969;Ödling et al 2006;Stewart et al 2011;Kamino 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Such sessile organisms have developed specialised sensory systems that enable them to find optimal substrates via detection of surface physicochemical features (Clare & Nott 1994;Callow et al 2005;Aldred et al 2006;Bielecki et al 2009;Stewart et al 2011). Many fouling organisms, such as barnacles and mussels, have evolved adhesive secretions with superior abilities compared to synthetic glues, to attach to submerged surfaces with diverse properties (Nott 1969;Ödling et al 2006;Stewart et al 2011;Kamino 2013). These highly specialised glues thus allow fouling organisms to cope with the unpredictability of surfaces found in the marine environment (Nott & Foster 1969;Walker & Yule 1984;Aldred & Clare 2008;Aldred et al 2011;Maruzzo et al 2011).…”
Section: Introductionmentioning
confidence: 99%